START-UPS AND INTERNATIONALISATION: THE CASE OF ROMANIA. PART 1. THEORETICAL OVERVIEW - Anamaria Diana Herte (Oradea Journal of Business and Economics, 2020)
Within the general concept of companies, start-ups are, more practically than theoretically, a distinct category including the so-called newly born companies struggling for existence and confirmation. Although theories of start-ups are still emerging, it is known that these companies are set up to put in practice great ideas and they grow to reach the success desired by their founders. The definition is, from a strict scientific point of view, approximate and quite inconsistent, which is why the clarification of the category of start-ups can be done using contributions from the theories of management, organization, complexity, and entrepreneurship or life stages, while admitting that a clear picture of these entities is not yet available. Regardless of the multitude of perspectives, researchers and practitioners agree that growth is therefore an essential part in the development, consolidation and orientation of start-ups. It is therefore not uncommon to find that the vast majority of European start-ups are interested in internationalizing, or expanding their internationalization, in the immediate future, despite considerable difficulties and challenges, exacerbated by lack of experience and the market power of new companies. The situation of start-ups in Romania is a bit more complex and certainly not as enthusiastic – a series of constraints, objectives and subjective, make the expansion on new markets an option not as attractive for young small and medium Romanian companies.